PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA KELAS VII PADA MATERI BANGUN DATAR DI UPTD SMPN 7 PEMATANG SIANTAR - Putra Agustinus Pasaribu; Yanti Maria Marbun; Rick Hunter Simanungkalit (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model on the mathematical conceptual understanding of seventh-grade students on the topic of plane figures at UPTD SMPN 7 Pematang Siantar. The research employed a quantitative approach using an experimental method with a One-Group Posttest Design, involving a single class of 32 students who received instruction through the PBL model. The students’ conceptual understanding was then measured using tests and questionnaires. The research instruments included a questionnaire, test, and lesson plans (RPP).The data analysis showed that the PBL model had a positive and significant effect on students’ mathematical conceptual understanding. The simple linear regression analysis produced the equation Y = -30.663 + 1.593X, indicating that for every one-unit increase in students’ perception of PBL, their conceptual understanding score increased by 1.593 points. The coefficient of determination (R²) was 0.988, meaning that 98.8% of the variance in conceptual understanding was explained by students’ perceptions of PBL implementation, while the remaining 1.2% was influenced by other factors. The t-test results showed that the calculated t-value (48.912) was much greater than the critical t-value (2.042), with a significance value of 0.000 < 0.05, indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted.In conclusion, the PBL model is effective in improving students’ mathematical conceptual understanding, particularly in topics requiring strong conceptual grasp such as plane figures. The implementation of this model is highly recommended in junior high school mathematics instruction to create an active, contextual, and student-centered learning environment.